An Error Analysis of English Article Usage (A, An, The, and Zero Article) in Translation Tasks by Advanced EFL Learners - Devi Adelia; Siti Ismahani; Aghna Ilmi Parinduri; Nurul Anisya Ray; Ibtisamah Nasywa; Qoeddri Farhansyah (Lembaga Riset Ilmiah, 2025)
This study investigates the usage errors of English articles (a, an, the, and zero article) in translation tasks among advanced Indonesian EFL learners. Utilizing a quantitative error analysis approach, the research involved 21 students from the English Education Department. Findings reveal that addition errors (64.4%) were the most prevalent, followed by substitution errors (33.3%) and omission errors (2.2%). Despite expectations, differences in accuracy between 5th and 7th semester students were minimal, indicating persistent first language interference in article usage. Students perceived English articles, particularly the zero article, as moderately difficult, primarily due to the absence of an article system in Indonesian. The study highlights the need for more comprehensive instruction focusing on the functional and phonetic aspects of articles to improve learners' grammatical accuracy in translation.